1994
DOI: 10.1897/1552-8618(1994)13[803:bateop]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

BIOCHEMICAL AND TOXIC EFFECTS OF POLYCHLORINATED BIPHENYLS (PCBs), DIBENZO-p-DIOXINS (PCDDs) AND DIBENZOFURANS (PCDFs) IN THE CORMORANT (PHALACROCORAX CARBO) AFTER IN OVO EXPOSURE

Abstract: Ecological investigations revealed differences in breeding success of cormorants (Phalacrocorax carbo) between two colonies in The Netherlands In this study the possible role of organohalogen pollutants was investigated. Thirty‐nine cormorant eggs were collected from two colonies with marked differences in contamination Seventeen cormorant eggs were hatched in an incubator. The respiration rate was monitored regularly during the incubation. Hatchlings were euthanized at day 1 Several morphological parameters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
5
4

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 31 publications
3
72
5
4
Order By: Relevance
“…Significant dose-dependent reductions in plasma thyroid hormone concentrations TT4 and FT4 were observed in cormorant hatchlings from high PCBcontaminated breeding colonies compared to those from low PCB-contaminated colonies (61). The number of hatchlings and fledglings in the high-contaminated breeding colony was significantly reduced compared to that in the low-polluted colony.…”
Section: Thyroid Hormone System Effectsmentioning
confidence: 90%
“…Significant dose-dependent reductions in plasma thyroid hormone concentrations TT4 and FT4 were observed in cormorant hatchlings from high PCBcontaminated breeding colonies compared to those from low PCB-contaminated colonies (61). The number of hatchlings and fledglings in the high-contaminated breeding colony was significantly reduced compared to that in the low-polluted colony.…”
Section: Thyroid Hormone System Effectsmentioning
confidence: 90%
“…However, the concurrent and similar results in the DTH and the antibody responses in the Baltic Sea group as Efforts to detect possible immunosuppression in free-ranging populations of marine mammals is fraught with difficulties due to the complexity of the mammalian immune system and the difficulty in obtaining reliable samples. However, field studies have demonstrated that it is possible to obtain useful immunological information from free-ranging seals (42,43), and correlative approaches similar to those used in wildlife toxicology (44) may provide the best direction for research in the future. …”
Section: Discussionmentioning
confidence: 99%
“…This study examined cormorant (Phalacrocorax carbo) hatchlings from two colonies with different levels of exposure to PCBs, PCDDs and PCDFs (van den Berg et al, 1994). A 50% difference in reproductive success was observed between the two colonies in the field, and the more contaminated colony had two to five times the level of PCBs and 25% more PCDD and PCDFs in yolk sacs.…”
Section: Thyroid Hormone and Retinoid Alterationsmentioning
confidence: 99%